Bioethanol production by the utilisation of Moringa oleifera stem with sono-assisted acid/alkali hydrolysis approach. (2016) - Sivarathnakumar, S.; Baskar, G.; Kumar, R. Praveen; Bharathiraja, B.
In this study, production of bioethanol was carried out by sono-assisted acid/alkali hydrolysis using the stem of Moringa oleifera. The woody stem was segregated and subjected to steam at reduce temperature for one hour residence time initially. Further acid and alkali treatment was carried out individually followed by combinations of acid and sonication, alkali and sonication. Sodium hydroxide, potassium hydroxide, hydrochloric acid, sulphuric acid and nitric acid were used with used with 3% (w/v) and 3% (v/v) concentration under temperature range of 60°C to 90°C for 60 min incubation time. Sonication under 60°C for 5 min and 40 kHz frequency was carried out. The increase in cellulose content and the decrease in lignin concentration were measured. The hydrolysate was further characterised using scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FTIR) to understand the changes in surface morphology and functional characteristics. The soft wood which when treated with sono assisted acid hydrolysis, the combination with nitric acid particularly at 70°C exhibited high amount of cellulose and low amount of lignin and no charring was found which was further taken for bioethanol production studies.